POOR COGNITIVE RESERVE STATUS AS PREDICTORS OF MEMORY IMPAIRMENT AMONG ELDERLY - Herpan Syafii Harahap; Yanna Indrayana (MNJ (Malang Neurology Journal), 2023)
Background: Cognitive impairment in the elderly population is commonly associated with age-associated neurodegenerative processes in the brain. The integrity of the cognitive reserve status may be an important factor that can compensate this age-associated neurodegenerative processes. Objective: To investigate the predictor role of poor cognitive reserve status on memory impairment among elderly subpopulation in Mataram, West Nusa Tenggara. Methods: This cross-sectional study involved elderly subjects recruited at Panti Jompo Tresna Werdha Puspa Karma. Data collected included age, gender, hypertension, diabetes, cognitive reserve status (years of education, leisure activity, occupation, and exercise), and memory status. Memory status obtained based on scores of 3 neuropsychological tests (wordlist memory task, recall, and recognition tests). Subjects with normal memory status had normal scores on at least 2 of the 3 neuropsychological tests. Multivariate regression analysis was performed to examine the role of cognitive reserve as a predictor of memory impairment in subjects. Results: In Model 1 of multivariate regression analysis, the main predictors for memory impairment in elderly subjects are shorter years of education (odds ratio: 13.1; 95% confidence interval: 1.8 – 95.0) and absence of leisure activity (odds ratio: 5.9; 1.2 – 28.8). In model 2, the main predictors for memory impairment are consistently shorter years of education (OR: 11.0; 95% CI: 1.4 – 84.0) and absence of leisure activity (OR: 5.3; 95% CI: 1.0 – 27.7). Conclusion: Shorter years of education and the absence of leisure activity were predictors for memory impairment in the subpopulation of the elderly in Mataram, West Nusa Tenggara.